Digital Transformation in Indonesian Life Insurance: Examining the Role of AI-Based Verification Capability in Enhancing the Relationship Between KYC Performance and Risk Assessment Accuracy - Alvin Ayodhia Siregar; Ceskakusumadewi Baharuddin; Sri Anawati (Universitas Negeri Surabaya, 2026)
Objective: This study examines how AI-Based Verification Capability, as a digital transformation capability, enhances the relationship between Know Your Customer (KYC) Performance and Risk Assessment Accuracy in Indonesian life insurance companies. The study addresses the growing need for insurers to improve customer due diligence, asset verification, fraud detection, and underwriting quality amid increasing regulatory requirements and digital transformation initiatives. Method: The study adopts a quantitative research approach using a cross-sectional survey of managers and executives working in underwriting, compliance, risk management, claims, information technology, and digital transformation functions within Indonesian life insurance companies. Data will be analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine direct and mediating relationships among the constructs. Results: The proposed model suggests that KYC Performance positively influences both AI-Based Verification Capability and Risk Assessment Accuracy. Furthermore, AI-Based Verification Capability is positively affecting Risk Assessment Accuracy and mediate the relationship between KYC Performance and Risk Assessment Accuracy. Organizations with stronger digital verification capabilities are deriving greater strategic value from KYC processes through enhanced data validation, fraud detection, and risk profiling. Novelty: This study contributes to the strategic management and digital transformation literature by conceptualizing AI-Based Verification Capability as a digital transformation capability that converts compliance-oriented KYC activities into strategic risk intelligence. The study extends Dynamic Capabilities Theory and Information Processing Theory within the context of the Indonesian life insurance industry.